PENGARUH ROE, DER, DAN PER TERHADAP RETURN SAHAM SYARIAH ISSI DENGAN INFLASI SEBAGAI MODERASI - Salwa Hanifah, (2023)
This study aims to examine the influence of profitability on stock prices in the sector of consumer goods and mining in the ISSI-year period 2012-2021. Profitability in this study uses Return On Equity (ROE), Debt to Equity Ratio (DER) and Price Earnings Ratio (PER). Where ROE, DER, and PER is the independent variable and profitability as the dependent variables. The population in the study here, namely the sector of property and real estate on the ISSI. The sample of this study using purposive sampling method. Data collection in this research is financial statements of the company sector of property and real estate which are listed in ISSI in the period from 2012 to 2021. Tool Test in this study is the Classical Assumption Test, the Analysis technique in this research is the Analysis of Panel Data Regression using the help of the application tool Eviews 10 and Microsoft Excel, and hypothesis testing statistical test t, test f statistic, and test the coefficient of determination. The results showed that ROE, DER, and PER variables have no effect on stock returns. This research is expected to contribute to potential investors in determining investment options in Islamic stocks, as well as in developing the Islamic capital market industry in Indonesia.